2014
DOI: 10.1542/peds.2013-3976
|View full text |Cite
|
Sign up to set email alerts
|

Developmental Pathways to Sexual Risk Behavior in High-Risk Adolescent Boys

Abstract: WHAT'S KNOWN ON THIS SUBJECT: Investigations of adolescents' sexual risk behavior have focused on factors such as parental monitoring, deviant peer affiliation, and daring that occur during early and midadolescence. Less is known about early childhood precursors to adolescent sexual risk behavior. WHAT THIS STUDY ADDS:This prospective longitudinal study identifies parenting practices and mothers' depressive symptomatology during early childhood as precursors to later sexual risk behavior and involvement in pre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
17
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(20 citation statements)
references
References 45 publications
2
17
0
1
Order By: Relevance
“…Fifth and finally, although the current study makes some important contributions to our understanding of how early impulsivity and parenting affect problem behaviors in adolescence and early adulthood, future research should identify more proximal mediating mechanisms that account for these links (e.g., Belsky et al, 2010;Dodge et al, 2009;Sitnick, Brennan, et al, 2014). In addition, the current study only used assessments of early impulsivity and rejecting parenting at age 2, but developmental psychopathology frameworks have emphasized the transactional nature of parent and child characteristics (Cicchetti & Valentino, 2006).…”
Section: Limitations and Directions For Future Researchmentioning
confidence: 98%
See 2 more Smart Citations
“…Fifth and finally, although the current study makes some important contributions to our understanding of how early impulsivity and parenting affect problem behaviors in adolescence and early adulthood, future research should identify more proximal mediating mechanisms that account for these links (e.g., Belsky et al, 2010;Dodge et al, 2009;Sitnick, Brennan, et al, 2014). In addition, the current study only used assessments of early impulsivity and rejecting parenting at age 2, but developmental psychopathology frameworks have emphasized the transactional nature of parent and child characteristics (Cicchetti & Valentino, 2006).…”
Section: Limitations and Directions For Future Researchmentioning
confidence: 98%
“…To our knowledge, this is the first study to establish that parenting assessed as young as age 2 has direct effects on sexual risk taking in adolescence and early adulthood. Previous longitudinal studies have found support for a link between harsh or neglecting parenting in the toddler or preschool years and later risky sexual behavior in adolescence through mediating processes, such as early pubertal timing in an all-girl sample and peer deviancy in a boys-only sample (Belsky et al, 2010;Sitnick, Brennan, et al, 2014). While we found evidence for direct effects of parenting, other more proximal processes are likely to show stronger associations with risky sexual behavior in adolescence and emerging adulthood, and future research should attempt to examine the specific mediating processes accounting for the association between early rejecting parenting and later risky sexual behavior.…”
Section: Pathways Toward Risky Sexual Behaviormentioning
confidence: 99%
See 1 more Smart Citation
“…12,13,1820 Furthermore, research suggests that parents value and seek out practical guidance from their adolescent children’s health care providers in supporting adolescent sexual and reproductive health. 15,16,21 Recently, some research has highlighted the importance of provider endorsement of effective parenting in support of adolescent health.…”
mentioning
confidence: 99%
“…Penelitian juga menunjukkan bahwa keterlibatan remaja atau dewasa dalam perilaku berisiko, baik sendiri maupun kelompok, dapat dideteksi mulai dari masa anak. Beberapa hasil penelitian telah menggambarkan bagaimana developmental pathway pada remaja yang melakukan perilaku berisiko, misalnya pada remaja laki-laki yang melakukan seks bebas (Sitnick, Brennan, Forbes, & Shaw, 2014), remaja dengan externalizing behavior (Reef, Diamantopoulou, Van Meurs, Verhulst, & Van Der Ende, 2011), dan remaja pecandu alkohol (Englund, Egeland, Oliva, & Collins, 2008 Kerig dkk., 2012). Para peneliti tersebut memberikan contoh tentang developmental pathway dari conduct disorder berdasarkan beberapa hasil penelitian, observasi, dan pengalaman mereka.…”
unclassified